2007
DOI: 10.1136/vr.160.12.404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the administration of flunixin meglumine on pregnancy rates in Holstein heifers

Abstract: Fifty-two 15-month-old Holstein heifers were synchronised with single or double injections of prostaglandin F(2alpha), followed by an injection of gonadotrophin-releasing hormone (gnrh) 48 hours later, and inseminated 12 to 14 hours after the injection of gnrh (day 0). Half of them were then injected twice intramuscularly with 1.1 mg/kg flunixin meglumine 12 hours apart, on the evening of day 15 and the morning of day 16, and the other 26 were not treated. Pregnancy was diagnosed by ultrasound 29 and 65 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 21 publications
1
30
1
Order By: Relevance
“…Failure of the conceptus to block luteolysis is one cause of pregnancy loss because administration of a PG synthesis inhibitor increased pregnancy rate in heifers (Guzeloglu et al 2007). The larger size and greater IFNT2 secretory activity of the CSF2-treated conceptus should improve its ability to prevent luteolysis and allow continuation of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of the conceptus to block luteolysis is one cause of pregnancy loss because administration of a PG synthesis inhibitor increased pregnancy rate in heifers (Guzeloglu et al 2007). The larger size and greater IFNT2 secretory activity of the CSF2-treated conceptus should improve its ability to prevent luteolysis and allow continuation of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In the reproductive sphere, its use is reported in studies related to female bovine, reducing PGF 2α production, increasing pregnancy rates in heifers (GUZELOGLU et al 2007) and increasing in vitro production of embryos (KIM et al 2014). …”
Section: Resultsmentioning
confidence: 99%
“…One prostaglandin, Flunixin Meglumine, has stood out due to its modulation activity in the production of PGF 2α , which has been useful to extend the luteal phase in the estral cycle of sheep (AKÉ-LOPEZ et al, 2005) and to assist biotechniques, such as embryo transfer in bovines (CARDOSO, 2009) and to improve pregnancy rates in reproductive protocols of heifers (GUZELOGLU et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Koblischke et al detected higher pregnancy rates of mares receiving flunixin meglumine and vedaprofen simultaneously when compared to untreated mares [5]. In cattle, administration of flunixin meglumine at the time of embryo transfer or before maternal recognition of gestation increased pregnancy rates according to Scenna et al [6] and Guzeloglu et al [11] although, similar studies did not show beneficial effects of flunixin meglumine treatment in bovines [12,13]. In mice, it has been shown that flunixin meglumine has no detrimental effects on embryonic survival and implantation [14], but possible beneficial effects of flunixin meglumine or other NSAIDs in pregnancy have not been reported yet.…”
Section: Introductionmentioning
confidence: 98%